2001
DOI: 10.1007/s005720100124
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the sporulation dynamics of arbuscular mycorrhizal fungi in monoxenic culture

Abstract: Spore production of arbuscular mycorrhizal fungi is important in inoculum production, and monoxenic culture is a promising way to produce large amounts of contaminant-free inoculum. Mass production of spores is therefore essential and mathematical models useful as descriptive and predictive tools of sporulation dynamics. We followed the sporulation dynamics of three Glomus strains i.e. G. intraradices, G. proliferum and G. caledonium, cultured monoxenically on a nutrient agar medium containing macro-and microe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(9 citation statements)
references
References 14 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…In order to estimate growth latency and growth rate for each strain and parameter tested, we performed a primary modelling step with the MatLab software (R2018b, Natick, Massachusetts: The MathWorks Inc.; see Figure 2a). We fitted a growth curve to the measured values for each strain and tested parameter using the modified Gompertz Equation () (Zwietering et al, 1990), as it is the most robust for fungal growth modelling (Declerck et al, 2001; Savary et al, 2022). ygoodbreak=y0goodbreak+agoodbreak×exp0.25em][goodbreak−exp0.25em][)(μnormalm×exp1a)(λgoodbreak−tgoodbreak+10.25emwhere y 0 is the value for time 0, y is the turbidity signal (in RNU) measured at time t , a is the maximal amplitude of the turbidity signal in RNU, μ m is the growth rate (RNU.h −1 ) in the exponential phase (hereafter called “maximal growth rate” as typically done in modelling growth studies) and λ is the lag time in hours (i.e., the time before fungal growth is detected).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to estimate growth latency and growth rate for each strain and parameter tested, we performed a primary modelling step with the MatLab software (R2018b, Natick, Massachusetts: The MathWorks Inc.; see Figure 2a). We fitted a growth curve to the measured values for each strain and tested parameter using the modified Gompertz Equation () (Zwietering et al, 1990), as it is the most robust for fungal growth modelling (Declerck et al, 2001; Savary et al, 2022). ygoodbreak=y0goodbreak+agoodbreak×exp0.25em][goodbreak−exp0.25em][)(μnormalm×exp1a)(λgoodbreak−tgoodbreak+10.25emwhere y 0 is the value for time 0, y is the turbidity signal (in RNU) measured at time t , a is the maximal amplitude of the turbidity signal in RNU, μ m is the growth rate (RNU.h −1 ) in the exponential phase (hereafter called “maximal growth rate” as typically done in modelling growth studies) and λ is the lag time in hours (i.e., the time before fungal growth is detected).…”
Section: Methodsmentioning
confidence: 99%
“…In order to estimate growth latency and growth rate for each strain and parameter tested, we performed a primary modelling step with the MatLab software (R2018b, Natick, Massachusetts: The MathWorks Inc.; see Figure 2a). We fitted a growth curve to the measured values for each strain and tested parameter using the modified Gompertz Equation (1) (Zwietering et al, 1990), as it is the most robust for fungal growth modelling (Declerck et al, 2001;Savary et al, 2022).…”
Section: Fungal Growth Kinetic Follow-up and Modellingmentioning
confidence: 99%
“…Numerous field and greenhouse experiments have shown the effects of mycorrhizal fungi on stomatal conductance, the rate at which CO 2 enters and water exits the leaf, with higher stomatal conductance in drought vs. well-watered conditions (Augé, 2001;Augé et al, 2015). While adverse abiotic conditions reduce AM fungal diversity compared to non-disturbed soil, some AM fungi exhibit opportunistic life history strategies including investing energy into spore production (Declerck et al, 2001) and, in the case of Rhizophagus irregularis, rapidly colonizing plant roots after disturbance (Sýkorová et al, 2007). In the green roof survey samples, the three most abundant OTUs in Glomeromycota aligned to Rhizophagus irregularis, which occurs in high relative abundance with Asteraceae plants (Wehner et al, 2014), and have previously been observed in green roof fungal communities in New York City (McGuire et al, 2013).…”
Section: Soil Microbial Community Compositionmentioning
confidence: 99%
“…Furthermore, AMF from different clades can develop differently depending on favorable or unfavorable environmental conditions [222] by adopting completely divergent resource-use strategies (R or K strategies), also known as "Life History Strategies" (LHS) [223][224][225]. For example, AMF from the Glomeraceae family allocate resources to grow mainly inside roots, forming structures such as arbuscules, vesicles, hyphae [226], reproducing quickly [227] and sporulating abundantly [228]. De facto, Glomeraceae can develop even under an unstable environment (R strategies) [223].…”
Section: Limits To the Amf-inoculum Application As Biocontrol Agentsmentioning
confidence: 99%